200 AFFINITY: opicinumab in a targeted population of MS patients. Issue 12 (14th November 2019) - Zhu, Bing; Calabresi, Peter A; Giovanonni, Gavin; Kapoor, Raj; Naismith, Robert; Hartung, Hans-Peter; Arnold, Douglas L; Wolstencroft, Paul; Johnson, Kristina
Abstract : Introduction: Opicinumab is a human monoclonal antibody against LINGO-1, a negative regulator of oligodendrocyte differentiation and axonal regeneration. The phase 2 SYNERGY study identified a patient subpopulation with a potentially enhanced response to opicinumab treatment. Methods: AFFINITY (NCT03222973 ) is an ongoing, randomised, double-blind, placebo-controlled phase 2 study to evaluate the efficacy/safety of opicinumab vs placebo as an add-on to disease-modifying therapies in a targeted population. Inclusion criteria include: age 18–58; relapsing multiple sclerosis (MS) with ≤20-year duration; Expanded Disability Status Scale (EDSS) score 2.0–6.0; evidence of disease activity within 24 months prior to enrolment; brain MRI criteria suggestive of low myelin content but preserved tissue integrity in pre-existing T2 lesions; stably treated ≥24 weeks with interferon-beta, dimethyl fumarate, or natalizumab. Primary endpoint is the multicomponent Overall Response Score (based on EDSS, Timed 25-Foot Walk, and 9-Hole Peg Test). Secondary endpoints will evaluate confirmed improvement in disability measures. Results: Enrolment began in September 2017 and was completed in September 2018. Participant baseline demographic, disease, and MRI characteristics will be presented. Conclusions: AFFINITY will further investigate the efficacy and safety of opicinumab in a subpopulation of MS patients. Support: Biogen. Disclosures to be included on poster.